Development of a Tablet Computer Application for HIV Testing and Risk History Calendar for Use With Older Africans - Parvin, Dilruba; Mosa, Abu Saleh Mohammad; Knight, Lucia; Schatz, Enid J. (Frontiers in Reproductive Health, 2021)
Life history calendars (LHCs) are able to capture large-scale retrospective quantitative data, which can be utilized to learn about transitions of behavior change over time. The Testing and Risk History Calendar (TRHC) is a version of life history calendar (LHC) which correlates critical social, sexual and health variables with the timing of HIV testing. In order to fulfill the need for time-bound data regarding HIV testing and risk of older persons in South Africa, a pilot of the TRHC was performed using a paper fold-out grid format. Though the TRHC study in this format was effective as older persons were able to recall details about their HIV testing and risk contexts, the interview process was tedious as data were collected manually. Development of a tablet application for TRHC study will improve data quality and make data entry and collection more automated. This paper presents the development of the TRHC application prototype in order to collect TRHC data electronically and provides a platform for efficient large-scale life history calendar data collection.